Bioprosthetic valve thrombosis after transcatheter aortic valve replacement and pulmonary embolism due to heparin-induced thrombocytopenia: a case report - Faucher, Loïc; Marchandot, Benjamin; Carmona, Adrien; Ohana, Mickael; Trimaille, Antonin; Morel, Olivier (Frontiers in Cardiovascular Medicine, 2023)
Background Bioprosthetic valve thrombosis is a complication of transcatheter aortic valve replacement (TAVR). It is believed to be platelet independent, mainly driven by contact phase activation, and more likely to be targeted by oral anticoagulant (OAC). Case summary We report case of an 86-year-old man with history of Transcatheter aortic valve replacement (TAVR), who presented an early TAVR aortic valve thrombosis occurring in the context of heparin induced thrombocytopenia (HIT), and pulmonary embolism. The patient rapidly recovered, and was discharged seventeen days after readmission. Oral anticoagulant (OAC) by Coumadin was administered for three months. A chest tomography after 3 months shown a disappearance of the hypoattenuated leaflet thickening (HALT). Discussion Although HIT has been fully described and is known for being a prothrombotic disorder this is the first case report of aortic valve thrombosis after TAVR due to HIT. HIT is rare but possibly lethal. Diagnosis is based on pre-test probability evaluation with 4T’s clinical score and confirmation with laboratory evidence of anti-PF4/heparin complexes and positivity of a functional test. Management of HIT is based on heparin discontinuation, and treatment of thrombotic complication with direct anti-IIa inhibitor or Anti-Xa inhibitor. According to our knowledge, this case represents the first report of biosprothetic valve thrombosis after TAVR due to HIT.